THE RATE OF METABOLIC SYNDROME AND COMORBIDITIES IN PATIENTS WITH GOUT: DATA OF A MULTICENTER TRIAL - V G Barskova; Maksim Sergeyevich Eliseyev; I S Denisov; M E Eliseyeva; O A Belikov; G R Fadiyenko; F S Zharskaya; O P Polkovnikova; A N Kalyagin; M V Sklyanova; E A Shvetsova; L A Knyazeva; et al. (Научно-практическая ревматология)
Objective: to study the rate of metabolic syndrome (MS) and its components among gout patients in different regions of the Russian Federation. Subjects and methods. This cross-sectional multicenter study enrolled 2277 gout patients, including 1963 (86.2%) men and 314 (13.8%) women, from 12 independent medical centers in different regions of the Russian Federation. The patients over 18 years of age who met the classification criteria for gout, elaborated by S. Wallace et al., were included. The diagnosis of MS was established on the basis of Adult Treatment Panel III (ATP III) criteria. The presence of MS, its individual components and comorbidities were recorded. Results. The total rate of MS in the patients with gout was 57%; however, it varied substantially (from 15 to 77%) in different centers. Among the comorbidities, arterial hypertension was most common (in three fourths of the patients), coronary heart disease (CHD) and type 2 diabetes mellitus were less common (43 and 25%, respectively); 15% of the patients had sustained myocardial infarction, renal and cardiac failure was also observed in 15%. In the gout patients, MS was associated with the presence of CHD. Conclusion. The patients with gout were observed to have a high rate of MS (57%), its components, and cardiovascular diseases. The findings suggest that there is a relationship between the presence of MS and the development of CHD.